Emerging point-of-care technologies for sickle cell disease screening and monitoring. (1st December 2016) - Alapan, Yunus; Fraiwan, Arwa; Kucukal, Erdem; Hasan, M. Noman; Ung, Ryan; Kim, Myeongseop; Odame, Isaac; Little, Jane A.; Gurkan, Umut A.
ABSTRACT: Introduction: Sickle Cell Disease (SCD) affects 100, 000 Americans and more than 14 million people globally, mostly in economically disadvantaged populations, and requires early diagnosis after birth and constant monitoring throughout the life-span of the patient. Areas covered: Early diagnosis of SCD still remains a challenge in preventing childhood mortality in the developing world due to requirements of skilled personnel and high-cost of currently available modalities. On the other hand, SCD monitoring presents insurmountable challenges due to heterogeneities among patient populations, as well as in the same individual longitudinally. Here, we describe emerging point-of-care micro/nano platform technologies for SCD screening and monitoring, and critically discuss current state of the art, potential challenges associated with these technologies, and future directions. Expert commentary: Recently developed microtechnologies offer simple, rapid, and affordable screening of SCD and have the potential to facilitate universal screening in resource-limited settings and developing countries. On the other hand, monitoring of SCD is more complicated compared to diagnosis and requires comprehensive validation of efficacy. Early use of novel microdevices for patient monitoring might come in especially handy in new clinical trial designs of emerging therapies.